Educational needs for nursing manager competency in Korean hospitals: multi-center cross-sectional study - Seung-Min Lee; Beob-Wang Ahn; Mi Yu (BMC Nursing)
Abstract Background Nursing managers have a critical responsibility for high-quality care, nursing staff support, and business operations for hospital outcomes. As the healthcare environment has changed, the role of nursing managers and the competencies required have evolved. This study aims to assess the educational needs for nursing management competency among 155 nursing managers in one tertiary and six general hospitals in South Korea. Methods Data were collected from April 1 to May 20, 2023, using self-reported questionnaires. The Borich needs assessment and locus for focus model were used to analyze educational needs. Results The results revealed that key components in the administrative manager (ensuring a safe working environment) and leader (fostering a positive workplace atmosphere) domains were most important. The lowest-scored item for performance was “Completing education to enhance competency as a manager and participating in external activities” in the educator domain. The most difficult item was “Allocation of appropriate nursing staff based on nursing requirements and adjustment of tasks” in the administrative manager domain. The top-priority items in administrative manager competencies were “Allocation of appropriate nursing staff based on nursing requirements, and adjustment of tasks” and “Development and implementation of plans for securing resources (staff, equipment, space, budget, etc.) necessary for nursing tasks.” Conclusions These findings underscore the necessity for nursing organizations to provide specialized training modules that address the identified needs, especially focusing on human resource management skills, the allocation of nursing staff, and resource acquisition and management for nursing managers. Furthermore, nursing organizations should support ongoing education and professional development activities through recognition, financial support, or career progression opportunities.